2001
DOI: 10.1089/10445460152595577
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label, Dose-Ranging Study of Atomoxetine in Children with Attention Deficit Hyperactivity Disorder

Abstract: These findings extend to children the positive results previously reported in adults diagnosed with ADHD who were treated with atomoxetine. These results support additional controlled trials of atomoxetine in cases of pediatric ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 6 publications
9
63
1
5
Order By: Relevance
“…When the data from the ADHD RS Total Score were examined using a visit-wise analysis, atomoxetine produced statistically significant efficacy at the first week after randomization that continued for the remainder of the study. These data demonstrating significant efficacy for atomoxetine in school-age girls with ADHD extend data from studies that have shown that atomoxetine is efficacious in boys and girls as well as in men and women with ADHD 15,16,24 (Spencer et al, unpublished data). In addition to demonstrating significant differences on investigator-scored measures, atomoxetine resulted in a significant decrease on a well-validated parentage rating scale, the CPRS-R.…”
Section: Discussionsupporting
confidence: 72%
“…When the data from the ADHD RS Total Score were examined using a visit-wise analysis, atomoxetine produced statistically significant efficacy at the first week after randomization that continued for the remainder of the study. These data demonstrating significant efficacy for atomoxetine in school-age girls with ADHD extend data from studies that have shown that atomoxetine is efficacious in boys and girls as well as in men and women with ADHD 15,16,24 (Spencer et al, unpublished data). In addition to demonstrating significant differences on investigator-scored measures, atomoxetine resulted in a significant decrease on a well-validated parentage rating scale, the CPRS-R.…”
Section: Discussionsupporting
confidence: 72%
“…Atomoxetine significantly reduced core symptoms of ADHD in an openlabel study in children . Overall, it was well tolerated in the child and adolescent age group (Michelson et al 2001;Spencer et al 2001). Atomoxetine has also been shown in a 6-week open label study to produce clinically significant improvement in the symptoms in patients with major depression (Chouinard et al 1984).…”
mentioning
confidence: 94%
“…Following a small open-label dose ranging study, 15 a large randomized controlled trial demonstrated superior effi cacy of 1.2 mg/kg/day and 1.8 mg/kg/day doses compared with placebo. 16 This multicenter 8-week trial included 297 children and adolescents with ADHD.…”
Section: Effi Cacymentioning
confidence: 99%